Integrasi Extended Failure Mode And Effect Analysis Pada Quality Improvement Matrix untuk Mendukung Peningkatan Kualitas - Aldiva Syawallad Akbar; Putu Dana Karningsih (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
Quality improvement in the manufacturing industry is generally carried out using various tools sequentially and in isolation. The Quality Improvement Matrix (QIM) has been developed as an integrated tool based on Failure Mode and Effect Analysis and Quality Function Deployment, aimed at quality improvement. The QIM analysis stages follow the logic of the House of Risk framework, but are modified for a different purpose namely to assist companies in analyzing defects, root causes of defects, and the prioritization of corrective actions. At present, the QIM still has several limitations: the assessment of Severity and implementation difficulty (Difficulty) do not explicitly account for cost factors. Furthermore, the QIM does not incorporate the Detection parameter, which is an important basis for developing corrective actions. This study proposes an enrichment of the QIM across three aspects. First, the integration of the Extended FMEA concept into the QIM by incorporating cost considerations into the Severity parameter through the Severity Cost (C) parameter, along with the addition of a Detection (D) parameter. Second, accommodating cost and time aspects in the assessment of the Difficulty parameter. Third, categorizing the root causes of defects based on Man, Machine, Method, Material, Measurement, and Mother Nature, with the aim of focusing the development of corrective actions. In addition, the corrective action stage (preventive action) emphasizes the use of Jidoka as one of the available improvement methods. The developed framework is then applied to a case study of a bogie manufacturer and validated through expert assessment within the company